Pendekatan Hermeneutik dalam Pengkajian Islam: Perspektif Pendidikan Agama Islam Kontekstual - Lutfiah Holifa Balkis; Amri Saputra; Winda Islamitha Nurhamidah; Nur Azizatul Haqiah; Ahmad Arifi (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the application of the hermeneutical approach in Islamic studies from the perspective of contextual Islamic Religious Education (IRE). The problem underlying this research is the dominance of textual and normative learning patterns in Islamic education that are often disconnected from contemporary social and cultural realities. The study aims to describe the hermeneutic concepts of Fazlur Rahman’s “double movement” and Hans-Georg Gadamer’s “fusion of horizons” and to analyze their relevance in developing contextual IRE. This research employs a qualitative library research method by analyzing recent scientific literature (2021–2025) from national and international journals. The findings reveal that hermeneutics provides a methodological and philosophical foundation for transforming IRE from rote-based learning into reflective, dialogical, and contextual learning. This study concludes that hermeneutics can be used as a conceptual and practical framework to strengthen the relevance of Islamic education in addressing modern challenges. However, the study’s limitation lies in its theoretical nature, so further empirical research is recommended to test the effectiveness of hermeneutic-based pedagogical models in classroom settings.